DNA methylation in blood as a mediator of the association of mid-childhood body mass index with cardio-metabolic risk score in early adolescence - Jian V. Huang; Andres Cardenas; Elena Colicino; C. Mary Schooling; Sheryl L. Rifas-Shiman; Golareh Agha; Yinan Zheng; Lifang Hou; Allan C. Just; Augusto A. Litonjua; Dawn L. DeMeo; Xihong Lin; et al. (Epigenetics, 2018)
Obesity is associated with higher cardio-metabolic risk even in childhood and adolescence; whether this association is mediated by epigenetic mechanisms remains unclear. We examined the extent to which mid-childhood body mass index (BMI) z-score (median age 7.7 years) was associated with cardio-metabolic risk score in early adolescence (median age 12.9 years) via mid-childhood DNA methylation among 265 children in the Project Viva. We measured DNA methylation in leukocytes using the Infinium Human Methylation450K BeadChip. We assessed mediation CpG-by-CpG using epigenome-wide association analyses, high-dimensional mediation analysis, and natural effect models. We observed mediation by mid-childhood DNA methylation at 6 CpGs for the association between mid-childhood BMI z-score and cardio-metabolic risk score in early adolescence in the high-dimensional mediation analysis (accounting for 10% of the total effect) and in the natural effect model (β = 0.04, P = 3.2e-2, accounting for 13% of the total effect). The natural direct effect of BMI z-score on cardio-metabolic risk score was still evident (β = 0.27, P = 1.1e-25). We also observed mediation by mid-childhood DNA methylation at 5 CpGs that was in the opposite direction from the total effect (natural effect model: β = −0.04, P = 2.0e-2). Mediation in different directions implies a complex role of DNA methylation in the association between BMI and cardio-metabolic risk and needs further investigation. Future studies with larger sample size and greater variability in cardio-metabolic risk will further help elucidate the role of DNA methylation for cardio-metabolic risk.